Low-carbon operation optimization of integrated energy system considering CCS-P2G and multi-market interaction - Qin, Lidong; Ma, Hengrui; Huang, Cunqiang; Li, Hongxia; Wu, Shidong; Wang, Gangfei (Frontiers in Energy Research, 2024)
Integrated energy system is crucial in realizing China's "dual carbon" targets. Considering the carbon capture based electricity to gas and the interaction of multiple markets, this paper proposes a lowcarbon operation optimization method of integrated energy system. In terms of market policy, a coupling trading mechanism for carbon trade and green certificates is established. This approach is intended to delve into the profound significance of utilizing green certificates in carbon emission reduction. In terms of equipment models, the coupling model of carbon capture equipment with coalfired cogeneration unit, as well as power-to-gas equipment with renewable energy, is con-structed. In addition, this equipment model is introduced into the operation optimization scheduling of the comprehensive energy systems. A low-carbon economic operational strategy is further proposed to minimize the daily operational costs, by which the integrated energy system is eco-nomically, environmental protection optimized. To verify the effectiveness and feasibility of the proposed model, this paper sets up several comparison scenarios and conducts the simulations using GUROBI solver. The results show that the proposed strategy can effectively improve the uptake rate of renewable energy, reduce the carbon emission, improve the operation economy, and realize the complementary incentive effect between markets.